Weibel-Palade body localized syntaxin-3 modulates von Willebrand Factor secretion fom endothelial cells - Schillemans, Maaike; Adam, Rüdiger (Arteriosclerosis, thrombosis, and vascular biology, 2018)
Objective: Endothelial cells store VWF (von Willebrand factor) in rod-shaped secretory organelles, called Weibel-Palade bodies (WPBs). WPB exocytosis is coordinated by a complex network of Rab GTPases, Rab effectors, and SNARE (soluble NSF attachment protein receptor) proteins. We have previously identified STXBP1 as the link between the Rab27A-Slp4-a complex on WPBs and the SNARE proteins syntaxin-2 and -3. In this study, we investigate the function of syntaxin-3 in VWF secretion. Approach and Results: In human umbilical vein endothelial cells and in blood outgrowth endothelial cells (BOECs) from healthy controls, endogenous syntaxin-3 immunolocalized to WPBs. A detailed analysis of BOECs isolated from a patient with variant microvillus inclusion disease, carrying a homozygous mutation in STX3(STX3−/−), showed a loss of syntaxin-3 protein and absence of WPB-associated syntaxin-3 immunoreactivity. Ultrastructural analysis revealed no detectable differences in morphology or prevalence of immature or mature WPBs in control versus STX3−/− BOECs. VWF multimer analysis showed normal patterns in plasma of the microvillus inclusion disease patient, and media from STX3−/− BOECs, together indicating WPB formation and maturation are unaffected by absence of syntaxin-3. However, a defect in basal as well as Ca2+- and cAMP-mediated VWF secretion was found in the STX3−/− BOECs. We also show that syntaxin-3 interacts with the WPB-associated SNARE protein VAMP8 (vesicle-associated membrane protein-8). Conclusions: Our data reveal syntaxin-3 as a novel WPB-associated SNARE protein that controls WPB exocytosis.
Gesehen am 27.06.2019
Originally published 1 Jul 2018